Pengaruh Kepuasan Kerja dan Komitmen Organisasi Terhadap Kinerja Karyawan - Riche Fermayani; Romi Rianto Harahap; Purnama Ramadhan (Jurnal Ecogen, 2023)
This study objective to find out the influence of job satisfaction and organizational commitment on employee performance at Bank Nagari Bukittinggi. Sample from this study were 87 respondents who were employees of Bank Nagari Bukittinggi Branch. Based on the partial t test, it can be seen that the job satisfaction variable has a significance value of 0.000 < 0.05, the conclusion is that the job satisfaction variable has a positive and significant effect on employee performance. The organizational commitment variable has a significance value of 0.000 < 0.05, the conclusion is that the organizational commitment variable has a positive and significant effect on employee performance. Based on the simultaneous f test, it is obtained a significance value of 0.000 < 0.05, the conclusion is that job satisfaction and organizational commitment as a whole have a significant effect on employee performance. The amount of influence of the independent variable on the dependent variable is 91.3%, the remaining 8.7% is influenced by variables other than the research model.